Factors Affecting Decision Making: Experience and Environment (Study Literature) - Mahaputra, M. Ridho (Dinasti Research, 2022)
A literature review article on the influence of experience and environment on decision-making is a scientific article that aims to build a research hypothesis on the influence between variables that it will use in further research within the scope of Human Resource Management. The method of writing this Literature Review article is the library research method, which is sourced from online media such as Google Scholar, Mendeley, and other academic online media. The results of this Literature Review article are that: 1) Experience influences Decision Making; 2) Environment influences Decision Making. Apart from these two exogenous variables that influence the endogenous variables of Decision Making, there are still many other factors, including the variables of Planning, Economic Policy, Communication, Motivation, Organizing, and Work Stress.